A role for seminal plasma in modulating pregnancy outcomes in domestic species. Issue 6 (December 2016) - Bromfield, John J
Abstract : Seminal plasma is a complex fluid produced by the accessory glands of the male reproductive tract. Seminal plasma acts primarily as a transport medium for sperm on its arduous journey through the male and then female reproductive tract following ejaculation. This spermatozoan expedition will hopefully result in the meeting of and resultant fertilization of an oocyte, perpetuating the genetic lineage of both sexes. Whereas seminal plasma has historically been perceived as only a transport medium providing a nutrient-rich fluid environment for sperm during this exchange of genetic material, new insights into a complex communication pathway between males and females has been unraveled in the past 30 years. This new research suggests seminal plasma as a method to promote early pregnancy success by modulating cellular and molecular adaptions of the maternal environment required to facilitate healthy, successful pregnancy outcomes. Whereas much work on this exciting new communication process has focused on mice and translation to human reproduction, here we review the current evidence in domestic species where artificial insemination in the absence of seminal plasma is routine. Improving artificial insemination in domestic species to optimize offspring health and productivity could have far-reaching impacts on agriculturally relevant species such as cattle, sheep, pigs and horses.